THE ROLE OF PSYCHOLOGICAL CHARACTERISTICS IN PATIENTS WITH BRONCHIAL ASTHMA (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Among internal diseases, bronchial asthma is one of the most important problems of theoretical and practical medicine. Epidemiological studies demonstrate a steady increase in the prevalence of bronchial asthma worldwide, which determines its high medical and social significance for society. The most challenging issues remain the prediction of the course and outcomes of bronchial asthma accompanied by mental disorders. Numerous studies indicate disturbances in the emotional sphere. Assessment of the psychological status of patients with bronchial asthma plays an important role in a comprehensive approach to the treatment of this disease. Given the chronic nature of asthma and possible complications, it is essential to regularly monitor the psychological condition of patients. In medical practice, bronchial asthma is associated with various psychosomatic interactions, including the presence of psychogenic triggers of bronchoconstriction attacks, unfavorable and aggravating mental disorders (anxiety, depression, asthenia), psycho-emotional reactions to the fact and nature of somatic disease (nosogenic reactions), as well as somatogenic disorders (symptomatic psychoses, complications of hormonal therapy).
Keywords: Bronchial asthma (BA), psychological status, emotional sphere.